Bride Price in the Patriarchal South Sudanese Society: A Legal Perspective. (15th October 2021) - Deng, Mark A W
Abstract: This article discusses bride price and numerous problems associated with it from a legal perspective. Two such problems, indeed, the most serious of all, are: (i) bride price objectifies and commodifies women, and this lowers women's status in society; and (ii) bride price violates a woman's freedom to choose who to marry as all but young girls, that is, those under the age of 18, are forced into marriage by their families for bride-wealth. Young girls who dare to resist can be tortured severely, or even put to death. These practices violate the Transitional Constitution of South Sudan 2011 and the Child Act 2008 under which 'customs' and 'traditions' that are harmful to women and children are explicitly prohibited. They are equally in conflict with regional and international human rights conventions that proscribe similar practices. In light of all these issues, the article recommends bride price to be abolished through legislative measures—i.e. for the Government of South Sudan to enact a law to criminalise bride price. While this suggestion is likely to be met with resistance, given how deeply culturally ingrained this practice is, what should be compelling for the government is securing women and children's rights and freedoms.